Estimation of risk factors influencing the results of treatment in patients with new-onset pulmonary tuberculosis - E. B. Tsybikova; E. N. Dolzhenko; L. I. Vinogradova; A. V. Kroshilin; T. P. Sabgaida (Туберкулез и болезни лёгких)
A demand arose for estimating the risk factors influencing the results of treatment for their objective assessment in patients with new-onset pulmonary tuberculosis.Objective: to estimate risk factors influencing the results of treatment in patients with new-onset pulmonary tuberculosis to provide a rationale for new approaches to their registration and treatment assessment.Subjects and methods. Information about 227 pulmonary tuberculosis patients registered to be treated in the Ryazan Regional Tuberculosis Dispensary in 2011 was obtained from the reporting forms of the Ministry of Health of Russia. For their analysis, an inquiry schedule consisting of 32 characteristics was worked out. The methods of a multifactorial analysis were applied.Results. The multifactorial analysis showed that there was a deep relationship between two factors: bacterial excretion and pulmonary cavitation. It was determined that the number of cohorts of pulmonary tuberculosis patients to be registered should be increased from 4 to 6. An effective treatment outcome, or clinical resolution, is indicative of the presence of two signs (cessation of bacterial excretion and closure of pulmonary cavities) and it is a uniform criterion for assessing the results of treatment in all patents with pulmonary tuberculosis regardless of the cohort they had been registered in. Changing a treatment regimen requires that the patient should be re-registered in another respective cohort.